Fenomena Ziarah Makam Pangeran Jayakarta di Jatinegara Pulo Gadung, Jakarta Timur - Rinka Sari; Trie Yunita Sari (Faculty of Ushuluddin Syarif Hidayatullah State Islamic University, 2024)
This research explores the tradition of visiting graves (ziarah) in Jakarta, Indonesia, focusing on the case of Pangeran Jayakarta's grave in Jatinegara Kaum, Pulogadung, Jakarta Timur. The study aims to understand the purpose, meaning, and spiritual effects of this practice among the urban community, particularly in the context of Jakarta Timur. The research draws on relevant literature, including Bambang Deliyanto's work on the preservation of cultural heritage sites in Jakarta Timur and M. Misbahul Mujib's study on the traditions of Javanese pilgrimage. The findings of this study are expected to contribute to a better understanding of the dynamics of religious and cultural practices in urban settings.